Use of microorganisms with biofertilizer potential in basil (Ocimum basilicum L.) crop - Wilches-Ortiz, Wilmar Alexander; Ramírez-Gómez, María Margarita; Serralde-Ordoñez, Diana Paola; Beltrán-Medina, José Isidro; Mendoza-Labrador, Jonathan Alberto; Estrada-Bonilla, Germán Andrés; Pedroza-Berrío, Kelly Johana; Hoyos-Cartagena, Jose Alvaro (Revista de Ciencias Agrícolas, 2025)
Basil (Ocimum basilicum L.) cultivation in Colombia is highly versatile in the market and requires technologies to increase its competitiveness and sustainability. The use of biofertilizers represents an efficient strategy to improve productivity. This study aimed to evaluate the effect of inoculating arbuscular mycorrhizal fungi (AMF): Claroideoglomus etunicatum and Gigaspora rosea; and the biofertilizers of plant growth-promoting bacteria (PGPB): Rhizobium leguminosarum, Azospirillum brasilense, and Herbaspirillum frisingense, Fosfotal®, and monibac®, individually and in mixtures on crop production. The experiment was carried out on a commercial farm using a randomized complete block design, three replications, and nine treatments. Results show higher aerial fresh biomass with the inoculation of G. rosea (T3), followed by C. etunicatum (T4), and its mixture with PGPB2 (T8 and T7). There were positive correlations between T3 and G. rosea and plant length, leaf area index, number of stems, and phosphorus uptake. Treatments 4 and 7 showed positive relationships with C. etunicatum and fresh and dry biomass, chlorophyll, nitrogen uptake, and stomatal conductance. Treatments 2 and 8 showed affinity with Azospirillum brasilense, Herbaspirillum sp., and Rhizobium sp., and the physiological variables of intrinsic and extrinsic water use efficiency and the ratio of net photosynthesis to intercellular carbon. It is concluded that AMF, individually or in mixture with PGPB, promotes the growth and development of basil plants, leading to increased fresh biomass production.